2017
DOI: 10.1038/cddis.2017.77
|View full text |Cite
|
Sign up to set email alerts
|

Targeted apoptosis in ovarian cancer cells through mitochondrial dysfunction in response to Sambucus nigra agglutinin

Abstract: Ovarian carcinoma (OC) patients encounter the severe challenge of clinical management owing to lack of screening measures, chemoresistance and finally dearth of non-toxic therapeutics. Cancer cells deploy various defense strategies to sustain the tumor microenvironment, among which deregulated apoptosis remains a versatile promoter of cancer progression. Although recent research has focused on identifying agents capable of inducing apoptosis in cancer cells, yet molecules efficiently breaching their survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 53 publications
(60 reference statements)
0
40
0
1
Order By: Relevance
“…The overexpression of ST6Gal1 in OVCAR4 OvCa cells that are exposed to cisplatin led to a reduction in Caspase-3 activation as measured by western blot analysis [57]. Additionally, targeting hypersialylated OvCa cells with α2, 6-linked sialic acid binding Sambucus nigra agglutinin (SNA) was shown to induce the apoptosis of IOSE-364 and SKOV3 OvCa cell lines [58]. SNA treatment was found to increase Bax and decrease Bcl-2 levels as well as increase levels of Caspase-3 and Caspase-9 as measured by western blot, to induce apoptosis [58].…”
Section: Regulation Of Ovca Apoptosis Via Glycosylation and Glycanmentioning
confidence: 99%
“…The overexpression of ST6Gal1 in OVCAR4 OvCa cells that are exposed to cisplatin led to a reduction in Caspase-3 activation as measured by western blot analysis [57]. Additionally, targeting hypersialylated OvCa cells with α2, 6-linked sialic acid binding Sambucus nigra agglutinin (SNA) was shown to induce the apoptosis of IOSE-364 and SKOV3 OvCa cell lines [58]. SNA treatment was found to increase Bax and decrease Bcl-2 levels as well as increase levels of Caspase-3 and Caspase-9 as measured by western blot, to induce apoptosis [58].…”
Section: Regulation Of Ovca Apoptosis Via Glycosylation and Glycanmentioning
confidence: 99%
“…There are several studies that have shown the effects of various non-chemotherapeutic agents on mitochondrial fission in ovarian cancer. Previous reports showed that phytochemical agents including piperlongumine, piceatannol, Sambucus nigra agglutinin (SNA), and cordycepin could induce both mitochondrial fission by decreasing p-Drp1 Ser637 and increasing Drp1 and Fis1 mRNA levels, and apoptosis by decreasing anti-apoptotic Bcl-2 and increasing pro-apoptotic regulators such as Bax and Cyt C levels; and caspase activity in both chemosensitive and chemoresistant ovarian cancer cells [ 18 , 34 , 35 , 38 ]. Interestingly, these phytochemicals also enhanced the cytotoxic effects of cisplatin when combination therapy was used.…”
Section: Evidence Of Mitochondrial Fission In Ovarian Cancer With Phamentioning
confidence: 99%
“…There are a limited number of studies regarding the effects of pharmacological intervention on mitochondrial fusion in ovarian cancer cell lines. Sambucus nigra agglutinin (SNA) and Cordycepin treatment led to mitochondrial dysfunction through suppressed mitochondrial fusion indicated by a decrease in expression of the fusion gene Mfn-1 and Mfn-2 in ovarian cancer cells [ 18 , 38 ]. Additionally, previous studies had indicated a correlation between nutrient stress and Bcl-2 anti-apoptotic proteins [ 42 ].…”
Section: Evidence Of Mitochondrial Fusion In Ovarian Cancer With Pharmentioning
confidence: 99%
“…Растворимые лектины коммуникаций участвуют в выборе и целевой доставке ГК, причём комплексные системы приобретают широкий регулируемый спектр антиопухолевых активностей, расширяют базу востребования организмом терапевтических лектиновых комплексов. Против различных опухолей в целевых доставочных процедурах применялись фитолектины GS-I и VVA, AAL и SNA; интерлектин1 (оментин); галектин3 и галектин9 [9,11,21,27,31,34,42]. Лектины пробиотических микроорганизмов перспективны как комплексные системы целевого воздействия на мукозальный иммунитет, в том числе в противоопухолевом направлении [1,2].…”
Section: цель обзораunclassified